Subjective evaluation of sound emitted by a loudspeaker system in correlation with its steady-state and transient responses - NIEWIAROWICZ, M.; FURMANN, A.; HOJAN, E.; PERZ, P. (Archives of Acoustics, 1998)
Objective parameters of a loudspeaker system, which describe its transmission properties in a transient- and steady-state, have been determined. These parameters have been related to the attributes of the sound perception space (fullness, clearness, sharpness, spaciousness, loudness, lack of distortions) with respect to the overall subjective evaluation and the parametric one. A good correlation between sharpness, fullness, spaciousness and selected objective parameters have been obtained. An influence of the test signal on the results of the subjective evaluation was also discovered.